Certain results on subordinations associated with a differintegral operator - Dziok, Jacek; Raina, Ravinder Krishna; Sokól, Janusz (MATHEMATICA SCANDINAVICA, 2011)
We investigate some interesting properties on subordinations for classes of multivalent analytic functions associated with a linear differintegral operator of J. Dziok [3]. Some applications and important consequences of the main results are also discussed.